(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Tourette’s syndrome is a neurodevelopmental disorder with emotional bases important for the manifestation of tics. This case report aims to describe the analytical-behavioral child psychotherapeutic care performed at a school clinic. Based on the functional analysis of problem behaviors, intervention techniques were used, such as habits reversal, DRO, social skills training and parental training. We count the tics of all sessions and divide them into two stages: observation and intervention, making the quartile. As a result, we saw that the lower range of tics in the first stage is significantly greater than the second. In addition, when comparing the ranges of minimum and maximum values ​​of the two stages, using the Mann-Whitney test, we found a significant difference (p = 0.0105). Therefore, it can be said that the interventions performed had an effective result. However, randomized and longitudinal clinical studies are needed to verify the effectiveness of the treatment in the medium and long term.